The Influence of Live Streaming, Brand Image, and Perceived Usefulness of Online Review on Purchase Intention on TikTok Shop - Hapipah Hapipah; Yasri Yasri (Journal of Business, Social and Technology, 2026)
Background: The rise of social media-based commerce—especially through TikTok Shop—has opened new avenues for brands to engage consumers through live streaming and peer-generated online reviews. Despite growing interest, the conditions under which these mechanisms drive purchase intention, and whether consumer trust mediates their effects for established FMCG brands, remain empirically underexplored. Objective: This study examines how live streaming, brand image, and perceived usefulness of online reviews influence purchase intentions on TikTok Shop, and assesses consumer trust as a mediating variable within these relationships. Methods: Survey data from 360 consumers who had watched Unilever’s live streaming sessions and made purchases on TikTok Shop were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, enabling simultaneous evaluation of direct and mediated pathways. Results: Live streaming exhibited a significant and direct effect on purchase intention. By contrast, brand image and perceived usefulness of online reviews produced no statistically significant direct effects. Consumer trust failed to mediate any of the three antecedent–outcome pathways, indicating that stimulus-driven direct routes dominate over sequential trust-based processes in this environment. Conclusion: Within live streaming–based social commerce, experiential immediacy and informational interactivity outweigh both brand image and consumer trust as purchase drivers. Practitioners should reposition live streaming as a primary conversion mechanism, and future researchers should interrogate the boundary conditions of trust’s motivational role in social commerce contexts.